Effect of exercise on quality of sleep in patients with ankylosing spondylitis - Lopes, Sofia (2015)
Ankylosing spondylitis (AS) is an inflammatory rheumatic disease, associated with limited mobility of the spine, sleep disturbance, and fatigue. The exercise aims are to preserve mobility and decrease sleep disorders.